Prospective assessment of the diagnostic utility of esophageal brushings in adults with eosinophilic esophagitis. Issue 1 (17th December 2014) - Kern, E.; Lin, D.; Larson, A.; Yang, G.‐Y.; Taft, T.; Zalewski, A.; Gonsalves, N.; Hirano, I.
Summary: Patients with eosinophilic esophagitis (EoE) undergo multiple endoscopies with biopsy for both diagnosis and assessment of treatment response, which is inconvenient and costly. Brush cytology has been examined in Barrett's esophagus to reduce the need for repeated endoscopic biopsies. The aim of this pilot study was to evaluate the ability of brush cytology to detect mucosal eosinophilia in patients with EoE. This prospective study included adults with untreated and treated esophageal eosinophilia undergoing endoscopy at a tertiary care center. Patients received paired brushings and biopsies at the proximal and distal esophagus. A blinded pathologist quantified the number of eosinophils and epithelial cells per high‐power field (hpf) on the cytology slides. The ratio of eosinophils/epithelial cells was used to normalize the cytology specimens for density of cells collected. The main outcome measures were sensitivity and specificity of brush cytology, and correlation between cytology and histology. Twenty‐eight patients enrolled. The average age of the cohort was 37.7 ± 10.4 years; 75% of subjects were male. The sensitivity of cytology was 67–69% at the proximal esophagus and 70–72% at the distal esophagus. The specificity was 61–67% proximally and 70–75% distally. Histology was not significantly correlated with the max ratio of eosinophils/epithelial cells per hpf or the absolute number of eosinophils on cytology slides. Cytology using esophageal brushing has limited sensitivity and specificity for the detection of esophageal mucosal eosinophilia. The presence of exudates on endoscopy increased the detection of eosinophilia, which could make cytology useful in pediatric EoE, which often has a more exudative presentation. Diagnostic yield may improve with alternative acquisition techniques or the incorporation of eosinophil degranulation proteins.